Assessment of Oxidative Stress Genes SOD2 and SOD3 Polymorphisms Role in Human Colorectal Cancer - MARGINEAN, C. (Curr Health Sci J, 2016)
Purpose: The aim of this study was to ascertain the oxidative stress genes SOD2 and SOD3 polymorphisms in patients with colorectal cancer and to assess the possible involvement of these polymorphisms that might increase the risk for patients to develop malignant intestinal tumors. Material and methods: A total number of 306 subjects were divided into two groups (109 colorectal cancer patients as the study group and 197 normal healthy individuals as the control group).We genotyped two polymorphisms, SOD2 – 201A>G (rs4880) and SOD3 – 896C>G (rs1799895), by allelic discrimination, with TaqMan RT-PCR specific probes. Results: No significant differences were found with either of the polymorphisms when comparing the association between them and an increased risk of developing colorectal tumors. Conclusion: In Romanian population, the risk of developing colorectal cancer is not increased by SOD2 and SOD3 polymorphisms.